The Effective Learning Models in Developing Problem-Solving Skills - Kharisma, Firlita Nurul; Susilowati, Sri Mulyani Endang; Ridlo , Saiful (KnE Social Sciences, 2019)
21st-century learning demands and the 2013 curriculum, master problem-solving skills. Learning model that will be tested PBL, PjBL, and DL with a scientiﬁc approach. This study aims, to ﬁnd out among the three learning models above, which learning model is the most effective for developing problem-solving skills. The research method used was quasi-experimental with the design of posttest-only control groups. The study population consisted of students seven classes of SMP 6 Petarukan the number is seven classes. Sample selection techniques using cluster random sampling obtained three classes for the experimental group and one for control. Data on problem-solving abilitiesaretakenusingmultiplechoicetestswithatotalof20item.Theresultsshowed: (1)therewerenosigniﬁcantdifferencesaboutstudents’abilityinproblem-solvingtaught byPBL,PjBL,andDLlearningmodels,butdifferedsigniﬁcantlyfromthecontrolgroup; (2) the effectiveness of the three learning models based on achievement from high to low is the PBL, PjBL, and DL models. Keywords: discovery learning, problem-solving ability, problem-based learning, project-based learning